Kinematic comparative analysis of short turns between skilled and unskilled alpine skiers - Jo, H. D. (Korean Journal of Sport Biomechanics, 2019)
Objective: The purpose of this study is to provide a better understanding of short turn mechanism by describing short turns after kinematic analysis and provide skiers and winter sports instructors with data through which they are able to analyze right postures for turns in skiing in a systematic, rational and scientific manner.